Pancreatic cancer in the United States: a retrospective study of incidence patterns - Ranganatha, Akash; Biswas, Deepanwita; Desai, Arusha D.; Ibrahim, Deka A.; Polanco, Manuel A. T.; Vartanian, Karine (International Journal of Research in Medical Sciences, 2025)
Background: The seventh most common cause of cancer-related deaths globally is pancreatic cancer. The 5-year survival rate for pancreatic cancer is about 12%, despite advances in its identification and treatment. The present study thus aims to perform an age, gender, race, and state-wise distribution trend analysis of pancreatic cancer incidence in the US from 1999 to 2020. Methods: The present study is a retrospective research study conducted using the CDC-WONDER database to investigate trends in pancreatic cancer incidence by age, gender, and race from 1999 to 2020. The data was extracted on 18 May 2024, based on temporal trends, demography, and exported to a Microsoft excel sheet. Statistical analysis was done using R version 4.3.1. The figures/graphs were created using GG plot 2, version 3.5.0. Results: From 1999 to 2020, pancreatic cancer occurred in 919,317 individuals (0.0137%) out of a population of 6,722,531,044, with a crude rate of 13.7 per 100,000. The highest incidence was observed in individuals over 75 years (38.63%), followed by the 65-74 age group (29.02%). Both males and females showed nearly equal incidence rates, while Whites had the highest incidence (83.76%), followed by African Americans (12.22%). Temporal trends indicate increasing incidence overall, particularly among the elderly and Whites, with state-wise highest incidences in California, Florida, and New York. Conclusion: In summary, the incidence of pancreatic cancer has been increasing for years. Analysis of pancreatic cancer epidemiology and modifiable risk factors can help to determine the preventive measures to reduce pancreatic cancer among the population worldwide.